2019
DOI: 10.1186/s13578-019-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Metformin represses the pathophysiology of AAA by suppressing the activation of PI3K/AKT/mTOR/autophagy pathway in ApoE−/− mice

Abstract: Background: The protective effect of metformin (MET) on abdominal aortic aneurysm (AAA) has been reported. However, the related mechanism is still poor understood. In this study, we deeply investigated the role of metformin in AAA pathophysiology. Methods: Angiotensin II (Ang-II) was used to construct the AAA model in ApoE −/− mice. The related mechanism was explored using Western blot and quantitative real time PCR (qRT-PCR). We also observed the morphological changes in the abdominal aorta and the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 65 publications
(40 reference statements)
2
52
0
Order By: Relevance
“…Ang-II induced autophagy by increasing Beclin-1, Vps34, Atg-12-Atg5, Atg4 and Atg7 protein levels, Beclin-1 phosphorylation, and the number of autophagic vesicles [21]. Here, we found that Atg7 was up-regulated in Ang-II treated VSMCs, as our previous study showed that metformin represses the pathophysiology of AAA by inhibiting autophagy pathway [15], in this study, we showed that the induced expression of Atg7 in AAA was reversed by metformin. Until recently, there are no reports evaluating whether metformin regulate Atg7 in Ang-II induced VSMSs.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Ang-II induced autophagy by increasing Beclin-1, Vps34, Atg-12-Atg5, Atg4 and Atg7 protein levels, Beclin-1 phosphorylation, and the number of autophagic vesicles [21]. Here, we found that Atg7 was up-regulated in Ang-II treated VSMCs, as our previous study showed that metformin represses the pathophysiology of AAA by inhibiting autophagy pathway [15], in this study, we showed that the induced expression of Atg7 in AAA was reversed by metformin. Until recently, there are no reports evaluating whether metformin regulate Atg7 in Ang-II induced VSMSs.…”
Section: Discussionsupporting
confidence: 78%
“…More importantly, metformin prescription status may be associated with a decreased risk of AAA [28]. Recently, we demonstrated that metformin protected Ang-II induced AAA by activating PI3K/Akt/mTOR/autophagy pathway [15], however, it remained unclear the molecular mechanism under this pathway. In this study, by using in vitro AAA model, we provide evidence that autophagy induced by Atg7 was reversed by metformin, suggesting that metformin reduced autophagy through suppressing Atg7.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mTOR signaling pathway is closely related to tumors, and it is closely related to its cell growth, metabolism, apoptosis and autophagy [47,81]. For example, the mTOR signaling pathway can affect gene transcription and protein synthesis to regulate cell growth and proliferation, affect the immune cell differentiation to participate in immune regulation, and play an important role in tumor metabolism.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…The Quantitative reverse transcription-PCR was performed as previously described. 22 Total RNAs and miRNA were extracted using TRIzol and a miRNA isolation kit (Invitrogen, Waltham, MA, USA). The primers used were as follows: DLX6-AS1: F: 5′-AGTTTCTCTCTAGATTG CCTT-3′ and R: 5′-ATTGACATGTTAGTGCCCTT-3′; miR-26a: F: 5′-GGATCCGCAGAAACTCCAGAGAGA AGGA-3′ and R: 3′-AAGCTTGCCTTTAGCAGAAAGGA GGTT-5′; U6 primer: F: 5′-ATCCGCAAAGACCTGT-3′ and R: 5′-GGGTGTAACACTAAG-3′; and GAPDH: F: 5′-GGGAAATTCAACGGCACAGT-3′ and R: 5′-AGATGGT GATGGGCTTCCC-3′.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%